Revisiter les héritages des villes à l’aune de la révolution numérique : patrimoine domestique et dispositif digital, un mariage de raison ? - Maxime Schirrer (Netcom)
In 2006, the association of urban planning of the center of Paris (AUCP1234) initiated a reflection on the mobility and the service of the 1st, 2nd, 3rd and 4th districts of Paris. In 2018, this proposal is all the more relevant as it is part of a dynamic merger of the central districts of Paris to be achieved in 2020 and the preparation of the Games of 2024. The AUCP proposal is for the implementation of a small collective vehicle to better serve the neighborhoods of the center of Paris by offering more mobility to residents and a better connection between services, facilities, places of commerce. By imagining urban itineraries in the historic heart of Paris, even though these spaces are constantly being reformed, this project highlights the heritage issue of the built environment, designed primarily as a place. However, the inhabitants often ignore the heritage of the domestic architecture in which they live. Through this case study, we propose a reflection on heritage and urban routes in the light of the digital revolution: how digital tools can be used for a form of urban pedagogy towards tourists and inhabitants. Whether it is to live an ornamental heritage or a domestic architecture, the innovative devices are new ways to support the legacies of cities, for residents, assets or tourists. A variety of needs, uses and urban practices merge, mingle and participate in the decompartmentalization of spaces and temporalities.